Meta analisis kasus DBD dengan model parametrik dan nonparametrik di Kota Makassar - Muhammad Kasim Aidid; Muhammad Nadjib Bustan; Ansari Saleh Ahmar (Seminar Nasional LP2M UNM, 2019)
Dengue Hemorrhagic Fever (DHF) has become a real threat so that many researchers are interested in studying both using parametric or nonparametric models. The next problem is that more and more studies are carried out on a particular topic that increases the likelihood of variations in the results or conclusions of the study. Meta-analysis becomes a solution for various study findings that originally seemed contradictory and difficult to accumulate eventually becoming more integrative and systematic. After reviewing the results of the study, it was concluded that several things were integrated with the findings or results of research in dengue cases in Makassar city using parametric and nonparametric models as follows: (1) Determination of variables not yet showing strong indications based on health theory analysis related to DHF deep and rational. (2) Analysis of data and interpretation of results has indicated that it has been done with the correct statistical technique. (3) Leukocyte levels and hematocrit levels are independent variables that influence the cure rate of DHF patients in Makassar City. While gender is an independent variable which by the whole researcher states no significant effect on the rate of recovery of patients with DHF in Makassar City.